View of the entrance from the mandapa - Temples of India Project Team (Jio Institute, 2024)
View of the entrance (east-facing) of the present temple structure. The doorframe is carved with figures at the bottom which have withered with time and can only be seen upon close inspection. The uttaranga (upper section of the doorframe) resembles a carved wooden roof. Dentil ornamentation breaks the monotony of an otherwise simple entrance.